PELESTARIAN LINGKUNGAN MASYARAKAT DAYAK KIYU MERATUS BERBASIS KEARIFAN LOKAL PERTANIAN MANUGAL - Intan Metrayani Sidauruk (KRONIK : Journal of History Education and Historiography, 2022)
This research aims to analyze the local wisdom system of manugal agriculture carried out by the Dayak Kiyu Meratus tribe to preserve the environment and know the efforts in preserving local wisdom amid the current globalization. The research method is a case study, aimed at knowing the concept that the subject builds with a particular phenomenon or event. Dayak Kiyu Meratus people are a society that is harmonious with nature, because nature has provided a livelihood for them. This is manifested in the use of forest land, this tribe divides the forest into two, namely prohibition forest and agricultural forest. In the use of agricultural forests, this tribe for generations uses local wisdom manugal. This local wisdom system is believed to preserve the environment because the local wisdom of agriculture is an agricultural system to grow local varieties of rice on dry land which is done once a year. In manugal land selection is a very important thing. For this tribe forest land should not be carelessly used as land for manugal. There are several rituals that they do: mangirau gives offerings to the spirits of forest waiting ancestors, grows, asks permission for the spirits of ancestors to clear land. Before the manugal, they will surround the land three times, carrying incense while reciting a spell of pleading to the ancestors so that rice products are abundant and can be enjoyed by all family members and promise not to damage nature. Efforts are made to preserve nature with local wisdom manugal by teaching the next generation, to make good use of forest land, and teach the values contained in local wisdom manugal. Keywords: Local Wisdom, Environmental Preservation, Social Change.